Rancang Bangun Aplikasi Pemesanan Penjualan Secara Online (Studi Kasus Mitra 10 Wiyung Surabaya) - Wulansari, Novita; tyas, Ayuning; Susilo, Tegar Heru (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
Abstract:PT CMSS is a company that operates as a distributor of building materials. Mitra 10 has an assortment of products by category and type complete with a comfortable place. The booking process sales that occurred customers come to the store to make a reservation.The problem that occurs is when customers come to view and select items. When the desired item is not available then the customer will be disappointed. The Company does not have an online booking system that can simplify the customer. To overcome the problems above, the author made design sales online ordering application to facilitate customers. Researcher using Waterfall SDLC model that worked in gradually. In this application has 3 user is a customer, admin and manager.Applications have been made to fix the sales order problem. It can simplify the ordering process online sales.